The Meaning of Kaffah in the Qur'an (Comparative Study of the Interpretation of Ibn Kathir in the Book of Tafsir Al-Qur'an Al-'Adhim and Wahbah Al-Zuhaili in the Book of Tafsir Al-Munir of Surah Al-Baqarah Verse 208) - Mohammad Fattah; Nabilatul Wafa (Penerbit Hellow Pustaka, 2025)
In discussing the word kaffah in the Al-Qur'an, it is only found in one verse, the meaning is